The Analysis of Figurative Language in Audre Lorde’s Poem ‘From the House of Yemanjá’ - Ei Mon Kyaw (Educalitra: English Education, Linguistics, and Literature Journal, 2022)
The goal of this study was to categorize the various figurative language that Audre Lorde employed in her poem From the House of Yemanjá. The study of figurative languages such as Metaphor, Personification, Hyperbole, Simile, Metonymy, Synecdoche, Irony, Antithesis, Symbolism, Alliteration, Onomatopoeia, Litotes, Idiom, Allusion, and Paradox are the subject of this study. A content analysis strategy was employed in this study together with a qualitative methodology. The researcher served as the main analytical tool for figurative language. The results of the analysis showed that From the House of Yemanjá, a poem by Audre Lorde, employed figurative language (29) times. The researcher concludes that Lorde's use of figurative language to symbolize the sentences results in beautiful language. The majority of her poems discussed her past experiences, which were influenced by the history of prejudice against American-African women or black women.